Use of cassava skin and coconut husk as lost circulation material in water-based mud (2016)
During oil and gas drilling operations, lost circulation of die drilling fluid could result in higher operational expenses this makes it imperative to design the drilling fluid to be used so as to minimize the invasion of the drilling fluid into the formation. Several materials had been proposed for use as Lost Circulation Material (LCM) but the use of the cassava skin and coconut husk have not been investigated. Water based mud prepared from bentonite and water, was used for the mud formulation Cassava Skins (CSS), Coconut Husks (CCH) were sun dried, shredded and blended to obtain fine to coarse fibrous and flaky particles respectively, Ground Marble (GM) was used as the control. These were used in the different concentrations ranging from 5ppb to 25ppb for the various drilling mud sample, and analyzed in the laboratory for particle sizing (which depends on the type of loss zone) using particle size distribution of material with the densities of the various samples ranging between 8.6 to 8.9 ppg. The viscosity for the mud sample with no LCM (16 cp) was a little higher while a gradual (but not linear) increase was observed for the 5 ppb to 25 ppb concentrations. A lost circulation test procedure for high permeability and fractured loss zones was performed using a 300 microns pore size, 508 and 1016 micron fracture width at 1000 psi pressure differential and temperature of 120 c F. This study is aimed at examining the impact of these local Lost Circulation Materials (LCMs) - Coconut Husk and Cassava skin on the rheological and thixotropic properties o f a water based mud and its effectiveness as a loss circulation material under static condition. Although the LCMs had no significant effect on mud rheology, it passed the API acceptability test range for plastic viscosity and yield point.